Legal and organizational principles of person identification by appearance during the investigation of criminal offenses in Ukraine - Kryvoruchko, L. S.; Криворучко, Л. С.; Kucher, O.; Кучер, О.; Husieva, V. O.; Гусєва, В. О.; Timush, I.; Тимуш, І.; Timush, D.; Тимуш, Д.; Vlada Husieva (Amazonia Investiga. – 2022. – Vol. 11, Issue 56 (August). – P. 82-90, 2022)
Визначено правові та організаційні засади ідентифікації особи за ознаками зовнішності під час розслідування кримінальних правопорушень в Україні. Досліджено правові й організаційні аспекти пред’явлення для впізнання, проведення портретних експертиз, ідентифікації за суб’єктивними портретами. Сформульовано рекомендації щодо удосконалення чинного кримінального процесуального законодавства. Відзначено чинники, що негативно позначаються на реалізації досліджених методах ідентифікації особи за ознаками зовнішності.

The purpose of the study is to determine the legal and organizational basis for identifying a person based on appearance during the investigation of criminal offenses in Ukraine.In order to achieve the goal of the article, the authors used methods of synthesis and analysis. Statistical methods were also used, with the help of which the problems that make it impossible to carry out portrait examinations based on the materials of video recordings and photographs, as well as other revealing ones, are defined and displayed in percentage form. The logical method and the method of generalization were used when formulating the conclusions of the conducted research.The authors have determined the legal and organizational aspects of presentation for identification, conducting portrait examinations, and identification based on subjective portraits. Recommendations for improving the current criminal procedural legislation have been formulated. The factors that negatively affect the implementation of the researched methods of identification of a person based on appearance are determined.

Определены правовые и организационные основы идентификации личности по признакам внешности при расследовании уголовных правонарушений в Украине. Исследованы правовые и организационные аспекты предъявления для опознания, проведения портретных экспертиз, идентификации по субъективным портретам. Сформулированы рекомендации по усовершенствованию действующего уголовного процессуального законодательства. Отмечены факторы, негативно сказывающиеся на реализации исследованных методах идентификации личности по признакам внешности.
Правові та організаційні засади ідентифікації особи за ознаками зовнішності під час розслідування кримінальних правопорушень в Україні
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Криміналістика. Criminalistics. Криминалистика; Україна. Ukraine. Украина; ідентифікація особи; identification of the person; идентификация личности; ознаки зовнішності; signs of appearance; признаки внешности; впізнання; recognition; опознание; портретна експертиза; portrait examination; портретная экспертиза; фоторобот; identikit; publikatsii u WoS